2015
DOI: 10.1177/1403494815601525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of children whose parents have a substance use disorder: Findings from a Swedish general population survey

Abstract: Our results showed that a substantial number of children in Sweden have parents with a SUD and that it is important to consider both alcohol and drugs, when estimating the size of this group. Our findings call for further strategies to support these children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
1
20
0
1
Order By: Relevance
“…Recent Swedish studies demonstrate that approximately 3–4% of all children under the age of 18 years have experienced a parent's alcohol‐related disorder, using information on hospital discharge diagnoses and survey data with questions covering the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders to identify alcohol‐related disorders . British national surveys indicate that 6% of children aged under 16 years live with an adult who is a dependent drinker, using the Severity of Alcohol Dependence Questionnaire to identify alcohol dependence .…”
Section: Introductionmentioning
confidence: 99%
“…Recent Swedish studies demonstrate that approximately 3–4% of all children under the age of 18 years have experienced a parent's alcohol‐related disorder, using information on hospital discharge diagnoses and survey data with questions covering the 4th edition of the Diagnostic and Statistical Manual of Mental Disorders to identify alcohol‐related disorders . British national surveys indicate that 6% of children aged under 16 years live with an adult who is a dependent drinker, using the Severity of Alcohol Dependence Questionnaire to identify alcohol dependence .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, available international estimates suggest that 8-23% of all children have parents with mental health problems [1,2] while 8-30% grow up with at least one parent having alcohol drinking problems [3][4][5]. Estimates in Sweden are in line with these figures [6][7][8], which puts a large proportion of Swedish children at risk for many acute and long-lasting negative consequences such as poor mental health, substance use problems and poorer academic achievement [9][10][11][12][13][14][15]. For instance, parental mental health problems such as mood and anxiety disorder and depression appear to have a high and long-lasting risk for children to develop own depression, somatic morbidity and higher mortality [16,17], which may also be explained by genetic vulnerability [18].…”
Section: Introductionmentioning
confidence: 87%
“…Reasons for the variation in the figures may include how the problem is defined, the methodology of data collection, and cultural differences. In line with this, Swedish estimates have revealed that approximately 5 % of all children have at least one parent with a substance use disorder [ 23 ], while 17–20 % grow up in families where at least one parent has risky alcohol consumption or substance use problems [ 24 – 26 ]. Moreover, about 6 % of all Swedish children have at least one parent who has received inpatient psychiatric care [ 25 ].…”
Section: Introductionmentioning
confidence: 97%